Knowledge and correlates of use of safer conception methods among HIV-infected women attending HIV care in Uganda - Violet Gwokyalya; Jolly Beyeza-Kashesya; John Baptist Bwanika; Joseph K. B. Matovu; Shaban Mugerwa; Jim Arinaitwe; Dickson Kasozi; Justine Bukenya; Rosemary Kindyomunda; Glenn J. Wagner; Fredrick E. Makumbi; Rhoda K. Wanyenze (BMC, 2019)
Abstract Background Many people living with HIV would like to have children but family planning (FP) services often focus on only contraception. Availability of safer conception services is still very low in most low income countries. In this study we assessed the knowledge and use of safer conception methods (SCM) among HIV infected women in HIV care in Uganda to inform integration of safer conception in existing FP services. Methods Data were accrued from a nationally representative cross-sectional survey of 5198 HIV+ women aged 15-49 years from 245 HIV clinics in Uganda. Knowledge and use of safer conception methods and associated factors were determined. The measure of association was prevalence ratio (PR) with corresponding 95% confidence intervals, obtained using a modified Poisson regression via generalized linear models. All the analyses were conducted using STATA version 12.0. Results Overall knowledge of any safer conception method was 74.1% (3852/5198). However only 13.2% knew 3 to 4 methods, 18.9% knew only 2 methods and 42% knew only one method. Knowledge of specific SCM was highest for timed unprotected intercourse (TUI) at 39% (n = 2027) followed by manual self-insemination (MSI) at 34.8% (n = 1809), and pre-exposure prophylaxis (PrEP) at 24.8% (n = 1289). Knowledge of SCM was higher in the Eastern region (84.8%, P < 0.001), among women in HIV-discordant relationships (76.7%, p < 0.017), and those on ART (74.5%, p < 0.034). Overall, 1796 (34.6%) women were pregnant or reported a birth in the past 2 years-overall use of SCM in this group was 11.6% (209/1796). The odds of use of SCM were significantly lower in Kampala [adj. PR = 0.489(0.314, 0.764)] or Eastern region [adj.PR = 0.244; (0.147, 0.405)] compared to Northern region. Higher odds of SCM use were associated with HIV status disclosure to partner [adj.PR = 2.613(1.308, 5.221)] and sero-discordant compared to HIV+ concordant relationship [adj.PR = 1.637(1.236, 2.168)]. Pre-existing knowledge of any one SCM did not influence SCM use. Conclusions Knowledge and use of SCM among HIV+ women in care is low. Efforts to improve HIV status disclosure, integration of safer conception into FP and HIV services and regional efforts to promote sensitization and access to safer conception can help to increase uptake of safer conception methods.